Strengthening resilience through knowledge sharing and co-designing interventions in the Dolo Ado and Bokolmayo districts, Somali Region, Ethiopia - Mekuria, Wolde; Haile, Alemseged Tamiru; Ebrahim, Girma Yimer; Dessalegn, Mengistu; Taye, Meron Teferi; Ruckstuhl, Sandra (International Water Management Institute, 2025)
Co-designing research-for-development interventions with humanitarian organizations, government agencies, communities, experts, and policymakers promotes a participatory approach that tailors disaster resilience solutions to local needs, builds trust and evidence, and empowers refugees and host communities. With this in mind, we co-developed research-for-development interventions in refugee host community settings in Ethiopia. The co-design exercise was conducted using a workshop that combined presentations, breakout sessions, and a panel discussion. It gathered 27 participants and focused on four themes: nature-based solutions for addressing natural disasters and land productivity, flood hazard mapping, water access and availability for multiple uses, and evolving livelihood shifts and governance to improve resilience. The participants included (i) policy and decision-makers, such as government representatives (local, regional, national); (ii) humanitarian organizations, such as WFP and UNHCR, along with collaborating NGOs; and (iii) researchers and academics.